2012
DOI: 10.1586/ern.12.41
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal endogenous pain modulation is a shared characteristic of many chronic pain conditions

Abstract: The intensity of acute and chronic pain depends on interactions between peripheral impulse input and CNS pain mechanisms, including facilitation and inhibition. Whereas tonic pain inhibition is a characteristic of most pain-free individuals, pain facilitation can be detected in many chronic pain patients. The capability to inhibit pain is normally distributed along a wide continuum in the general population and can be used to predict chronic pain. Accumulating evidence suggests that endogenous pain inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
177
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(197 citation statements)
references
References 144 publications
11
177
0
9
Order By: Relevance
“…59 Communication between the prefrontal cortex, the PAG, and the rostral ventrolateral medulla seems to be crucial in these chronic conditions. Studies have shown that PAG activity is increased in animal models of irritable bowel syndrome (IBS), which might be indirectly linked to visceral hypersensitivity in this chronic painful condition.…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…59 Communication between the prefrontal cortex, the PAG, and the rostral ventrolateral medulla seems to be crucial in these chronic conditions. Studies have shown that PAG activity is increased in animal models of irritable bowel syndrome (IBS), which might be indirectly linked to visceral hypersensitivity in this chronic painful condition.…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…First, significant group differences only emerged at larger scale factors (SFs) beginning from SF 52 (Figure 2a,b). Second, counts of significant group differences within each scale factor-interval were SFs 1~50 (0), 51~60 (4), 61-70 (8), 71~80 (6), 81~90 (10), and 91~100 (14). SF 92 was the most frequent feature (count = 4) that differentiated the brain complexity of PDMs from CONs, followed by SF 81 and SF 99 (3 counts each) (Figure 2a).…”
Section: Pdms and Cons Had Similar Demographic Characteristics And Mementioning
confidence: 98%
“…For instance, it is widely recognized that affective factors like fear [264] and depression [140] are important to assess in pain patients, although the causal relationships are complex and difficult to disentangle [140,263]. The biopsychosocial model is consistent with the view of the brain as an active system that filters, selects and, through descending neural pathways, modulates nociceptive input from the periphery [153,154,179,231]. The biopsychosocial model is also consistent with the fact that pain is not just about an "inner" experience; pain is associated with behavioural changes, e.g.…”
Section: The Biopsychosocial Modelmentioning
confidence: 98%
“…Hence, strictly speaking, the concept of central sensitization should be restricted to the preclinical neurophysiological setting. Nonetheless, some authors use concepts like "central sensitivity syndromes" or "centralized pain" to characterize some of the clinical pain conditions listed above in this paragraph [48,231].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation